Determinants of Export Intensity among Small and Medium-sized firms: An empirical study based on the heterogeneity of their resources - Sandoval-Alvarez, Carlos (Estudios de Administración, 2022)
The purpose of this study is to examine plausible determinants of the firms’ Export Intensity from the perspective of the heterogeneity of its resources. We developed and tested empirically a research model by applying structural equation modeling techniques to a sample of 133 exporting SMEs. The findings suggest that the Export Intensity exhibited by firms appears to lie in its degree of managerial export commitment along with the intense use of cross-national-border partners. A firm’s resource availability to deal with foreign markets impacts Export Intensity indirectly. Export commitment seems to play a mediating role between a firm’s resource availability and the export intensity.